A new cause of spoilage in goose sausages. (September 2016) - Iacumin, Lucilla; Manzano, Marisa; Panseri, Sara; Chiesa, Luca; Comi, Giuseppe
Abstract: The aim of this work was to determine the microorganisms present and to investigate their metabolites that cause spoilage of many goose sausages produced in Friuli, a northeast region of Italy. The defect was observed by sensorial analysis using the "needle probing" technique; the spoiled sausages were unsafe and not marketable. Despite the addition of starter, the microorganisms, particularly enterococci and Enterobacteriaceae, grew during ripening and produced a large amount of biogenic amines; therefore, these sausages represented a risk to consumers. The production of those compounds was confirmed in vitro . Furthermore, a second cause of spoilage was attributed to moulds that grew during ripening; the fungi grew between the meat and casing, producing a large amount of total volatile nitrogen, and consequently an ammonia smell was present either in the ripening area or in the sausages. This is the first description of this type of defect in goose sausages. Highlights: Entrococci and moulds produced biogenic amines and off-odor, respectively. Moulds grew between meat and casing and produced acetic acid and total volatile basic nitrogen. Enterococci grew during ripening and produced mainly histamine and cadaverine. The presence of histamine and cadaverine created healthy problem for the consumers.